Malaysian oral health literacy training package @ Celik Literasi Kesihatan Mulut Malaysia (CeLiK-M). module 2: communication in Oral Health Literacy (OHL) - Rani, Haslina; Che Musa, Muhd Firdaus; Zabha, Azliza; Ruslan, Ruzawani; Mohd Jeffry, Sabrina Julia; Abdul Manab, Enny Esdayantey; Kamarozaman, Dewi Mayang Sari (Oral Health Programme, Ministry of Health, 2026)
This module is part of a training package that has been carefully designed as a trainer’s resource to strengthen oral health literacy among oral healthcare personnel in Malaysia. The primary objective of the package is to raise awareness on the importance of oral health literacy and to enhance the essential skills required to address oral health literacy challenges in professional practice. The module focuses on the critical role of effective communication in promoting oral health literacy. Participants will be introduced to key communication principles, methods, and techniques that support clear, respectful, and patient-centred interactions. The module highlights how communication styles and approaches influence patients’ understanding, engagement, and ability to act on oral health information. Participants will also develop skills to tailor communication strategies to different target audiences, including individuals and small or large groups. Common communication barriers and challenges encountered in oral health literacy contexts are examined, along with practical strategies to overcome them. Through this module, participants are guided to apply effective communication techniques that enhance comprehension and support informed decision making.